Qualidade de vida de crianças com asma: tradução para o português (cultura brasileira) e validação do questionário “Pediatric Quality of Life (PedsQL) Asthma Module” - Monteiro, Fernanda Pereira [UNIFESP] (2016)
The Pediatric Quality of Life (PedsQL) questionnaire is an instrument developed to measure the impact of asthma on health-related quality of life (HRQOL) in children and adolescents, aged 2-18 years. Objectives: to translate and adapt to Portuguese (Brazilian culture) the PedsQL Asthma Module for its use in children and adolescents with asthma, and to validate the adapted version and analyze its psychometric properties (validity and reliability). Methods: The translation process consisted of several stages: translation, conciliation versions, backtranslation, cognitive interview and field test. In this study we have applied the following instruments: PedsQL Asthma Module Child (applied to children and teenagers), PedsQL Asthma Module Parent (applied to those responsible), Pediatric Asthma Quality of Life (PAQLQ), Asthma Control Test (ACT) and Childhood Asthma Control Test (C-ACT) and a socioeconomic and personal information questionnaire. The total sample consisted of 200 children and adolescents with asthma enrolled in the allergy clinic of a specialized unit and their respective parents, which were divided into four groups according to age groups of PedsQL. Statistical analyzes were performed using the Excel and SPSS 18.0 software. Results: The correlations between the PedsQL Child and Parent PedsQL (r = 0.67), PedsQL Child and PAQLQ (r = 0.66) and between PedsQL Parent and PAQLQ (r = 0.64) were significant. To separately analyze the areas, the first PedsQL Child domain related to the disease correlated significantly with the three areas of PAQLQ, symptoms (r = 0.78), activities (r = 0.70) and emotional (r= 0.64 ), comparing the PedsQL answered by the children answered by those responsible for all areas were significant, the best result in the field on the disease (r = 0.77). By analyzing the responses of the PedsQL among children and parents by gender correlations were more significant in males (r = 0.72) than in females (r = 0.56). The age group between 5 and 7 years of age achieved stronger correlation with the PAQLQ (r = 0.79) than the group of 8 to 12 years (r = 0.63) and 13 to 18 years (r = 0.51). Cronbach's alpha coefficient for the Child and Parent PedsQL was 0.85 and 0.87, respectively. When applied at two different times to clinically stable children, high agreement in PedsQL answers were observed both among children and parents (93% and 91%, respectively) with Kappa values of 0.89 and 0.87. Conclusion: the translation of the PedsQL Asthma Module did not structurally modify the original questionnaire, even after grammatical corrections and adjustments. It proved to be of easy and quick application and did not require previous training and the scores were easy to calculate. We can conclude that the instrument is useful, valid, consistent and reproducible to assess HRQOL in children and adolescents with asthma.